Fast size-determination of intact bacterial plasmids using nanofluidic channels1. Issue 13 (7th July 2015) - Frykholm, K.; Nyberg, L. K.; Lagerstedt, E.; Noble, C.; Fritzsche, J.; Karami, N.; Ambjörnsson, T.; Sandegren, L.; Westerlund, F.
<x xml:space="preserve">Abstract</x> We demonstrate how circular bacterial plasmids can be automatically sized and discriminated from linear DNA fragments via stretching in nanochannels.